Friday

April 18, 2014

April 18, 2014

Posted by **Felicia** on Tuesday, October 30, 2012 at 5:13pm.

- algebra -
**Steve**, Tuesday, October 30, 2012 at 5:18pm√(2x+1) + x = 7

√(2x+1) = 7-x

2x+1 = 49 - 14x + x^2

x^2 - 16x + 48 = 0

(x-12)(x-4) = 0

x = 4 or 12

check:

√(2*4+1)+4 = √9 + 4 = 3+4 = 7

√(2*12+1)+12 = √25 + 12 = 5+12 = 17 BOO!

Why? Because this is true only if we take the -√: -5+12 = 7, but that's not the original equation. Squaring both sides allowed for using + or - √.

**Related Questions**

Algebra - Use the quadratic formula to solve the equation. Give exact answers: ...

Algebra - Rationalize each expression by building perfect nth root factors for ...

Math - What are the solution sets of the following 3 problems,the square root of...

Algebra - solve for x: square root 2x+3 = square root 6x - 1. A.) 1 B.) 2 C.) 3 ...

algebra - 1)Write the expression 9n^6+7n^3-6 in quadratic form,if possible A.9(n...

math - Nakim simplified 3 times the square root of 2x plus x times the square ...

Algebra - How do you work square root problems when there is a number outside ...

Math simplifying mixed radicals - Please help me simplify these following mixed ...

calculus - Evaluate lim as x-> 0 square root (x+1) - square root (2x+1) / ...

calculus - Evaluate lim as x-> 0 square root (x+1) - square root (2x+1) / ...